Comparing wind turbine aeroelastic response predictions for turbines with increasingly flexible blades. Issue 3 (1st May 2022) - Cao, Kathy; Shaler, Kelsey; Johnson, Nick
Abstract: Highly flexible blades are becoming more prevalent designs as a potential solution to the transportation challenges associated with large-scale wind turbine rotors. However, there is currently no quantitative definition of "highly flexible" blades. To further develop turbines with highly flexible blades, a precise definition of the term and accurate simulations of turbines with such blades are required. Assumptions made in the traditional aerodynamic model, Blade Element Momentum (BEM) theory, are violated in turbines with flexible blades. However, Free Vortex Wake (FVW) methods can more accurately model these turbine designs. Though more computationally expensive than BEM, FVW methods are still computationally tractable for use in iterative turbine design. The purpose of this work was to determine the blade flexibility at which BEM and FVW methods begin to produce diverging aeroelastic response results. This was accomplished by simulating the BAR-DRC reference turbine with increasingly flexible blades in a range of steady, uniform inflow conditions using OpenFAST, the National Renewable Energy Laboratory's physics-based turbine engineering tool. Blade-tip deflections confirmed that BEM and FVW results diverge as blade flexibility increases. For the 212 m rotor diameter turbine used in this study, the two methods largely agreed for smaller blade deflections. But their results differed by an average of 5% when the out-of-plane blade-tip deflections exceeded 5% of the blade length and in-plane blade-tip deflections exceeded 1.25% of the blade length, with percent differences approaching 25% at the largest deflections.